2017
DOI: 10.1016/j.stemcr.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Generation of “Off-the-Shelf” Natural Killer Cells from Peripheral Blood Cell-Derived Induced Pluripotent Stem Cells

Abstract: SummaryCurrent donor cell-dependent strategies can only produce limited “made-to-order” therapeutic natural killer (NK) cells for limited patients. To provide unlimited “off-the-shelf” NK cells that serve many recipients, we designed and demonstrated a holistic manufacturing scheme to mass-produce NK cells from induced pluripotent stem cells (iPSCs). Starting with a highly accessible human cell source, peripheral blood cells (PBCs), we derived a good manufacturing practice-compatible iPSC source, PBC-derived i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 33 publications
3
99
0
Order By: Relevance
“…Another approach is to specifically block CD16A cleavage by expressing a non‐cleavable version of the receptor, such as CD16A‐S197P, in engineered NK cells. Various autologous and allogeneic NK cell platforms could be utilized, including expanded cord blood or peripheral blood NK cells, NK cell lines, and stem cell‐derived NK cells, which offer different advantages . A potential limitation of this approach is that NK cells expressing non‐cleavable CD16A might be less efficient at serial killing of Ab‐coated tumor cells in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is to specifically block CD16A cleavage by expressing a non‐cleavable version of the receptor, such as CD16A‐S197P, in engineered NK cells. Various autologous and allogeneic NK cell platforms could be utilized, including expanded cord blood or peripheral blood NK cells, NK cell lines, and stem cell‐derived NK cells, which offer different advantages . A potential limitation of this approach is that NK cells expressing non‐cleavable CD16A might be less efficient at serial killing of Ab‐coated tumor cells in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Of importance is that several clinically successful tumor-targeting Abs utilize ADCC as a primary mechanism of action. 3,89 [92][93][94] A potential limitation of this approach is that NK cells expressing non-cleavable CD16A might be less efficient at serial killing of Ab-coated tumor cells in vivo. However, it is also possible that noncleavable CD16A may further stabilize and increase NK cell attachment to tumor cells in the tumor microenvironment for more effective killing of resilient cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, an effective clinically applicable off-the-shelf allogenic T-cell therapy should meet the following criteria: (i) expandable to a therapeutically relevant number under clinically compliant condition; (ii) do not cause graft-versus-host disease (GvHD); (iii) are able to target an array of cancers in a donor-unrestricted manner; (iv) are not rejected by the recipient's immune system; (v) can be stored under GMP conditions without hampering their function (10). There are reports on ACTs with a potential to be used as an off-the-shelf therapy, including NK-92 (14), primary NK cells (17), and gd T cells (18), due to their HLA-unrestricted antitumor toxicity and low risk of off-tumor toxicity. However, to the best of our knowledge, there has not been a report to show an ACT that can avoid host-versus-graft (HvG) rejection while fulfilling other requirements of off-the-shelf therapy without any genetic modification.…”
Section: Introductionmentioning
confidence: 99%
“…Genetically modifying peripheral blood NK cells by retroviral or lentiviral transduction at this point has been challenging (36). Embryonic stem cells and iPSCs can be differentiated into cytolytic NK cells in vitro (2831, 37), and these cells are highly amendable to genetic engineering (14, 30, 38, 39). Undifferentiated iPSCs were transduced to express CD64/16A using a sleeping beauty transposon plasmid for nonrandom gene insertion and stable expression.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that fusion proteins containing a human IgG Fc region, such as L-selectin/Fc, can also be captured by CD64/16A and this may provide further options for directing the tissue and tumor antigen targeting of engineered NK cells. Advantages of the NK92 and iNK cell platforms for adoptive cell therapies is that they can be readily gene modified on a clonal level and expanded into clinical-scalable cell numbers to produce engineered NK cells with improved effector activities as an off-the-shelf therapeutic for cancer immunotherapy (37, 38, 40, 41, 47).…”
Section: Discussionmentioning
confidence: 99%